Initiation of Early Empiric Treatment Based on Clinical Features and Early Obtainable CSF Indices Can Prevent Worse Prognosis in Childhood Meningitis (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):232-8.The abstract of this article is available on the PubMed website